An Activatable NIR‐II Nanoprobe for In Vivo Early Real‐Time Diagnosis of Traumatic Brain Injury. Issue 1 (19th November 2019) - Li, Chunyan; Li, Wanfei; Liu, Huanhuan; Zhang, Yejun; Chen, Guangcun; Li, Zijing; Wang, Qiangbin
Abstract: Traumatic brain injury (TBI) is one of the most dangerous acute diseases resulting in high morbidity and mortality. Current methods remain limited with respect to early diagnosis and real‐time feedback on the pathological process. Herein, a targeted activatable fluorescent nanoprobe (V&A@Ag2 S) in the second near‐infrared window (NIR‐II) is presented for in vivo optical imaging of TBI. Initially, the fluorescence of V&A@Ag2 S is turned off owing to energy transfer from Ag2 S to the A1094 chromophore. Upon intravenous injection, V&A@Ag2 S quickly accumulates in the inflamed vascular endothelium of TBI based on VCAM1‐mediated endocytosis, after which the nanoprobe achieves rapid recovery of the NIR‐II fluorescence of Ag2 S quantum dots (QDs) owing to the bleaching of A1094 by the prodromal biomarker of TBI, peroxynitrite (ONOO − ). The nanoprobe offers high specificity, rapid response, and high sensitivity toward ONOO −, providing a convenient approach for in vivo early real‐time assessment of TBI. Abstract : TBI TBD : A targeted activatable NIR‐II nanoprobe (V&A@Ag2 S) that specifically lights up the traumatic brain injury (TBI) regions is presented. The nanoprobe response is based on the prodromal biomarker peroxynitrite (ONOO − )‐triggered fluorescence recovery, providing a favorable approach for in vivo early real‐time assessment of TBI.